CO2 capillary trapping in layered sandstone dominated by inertial force and gravity - Yingwen Li; Yongfei Yang; Mingzhe Dong (Capillarity, 2024)
Capillary trapping is an important strategy to prevent CO2 from escaping. Meanwhile, under immiscible conditions, CO2 may travel upwards by gravity. Studying the long-term effects of gravity and layered heterogeneity on CO2 transport is crucial for ensuring CO2 storage security in aquifers. In this work, fluid flow experiments driven by inertial force and gravity are conducted in a specially constructed layered sandstone. Whether driven by inertial force or gravity, the variation in CO2 distribution in the high-permeability layer is consistently the most significant factor. In the low-permeability layer, the saturation and capillary pressure distribution of CO2 clusters vary less and the geometric shapes are also more complex, thus the CO2 capillary trapping in this layer is more stable. This work demonstrates that the low-permeability layer can effectively prevent CO2 from escaping upwards when the permeability ratio between layers approaches two. Document Type: Short communication Cited as: Li, Y., Yang, Y., Dong, M. CO2 capillary trapping in layered sandstone dominated by inertial force and gravity. Capillarity, 2024, 10(1): 22-28. https://doi.org/10.46690/capi.2024.01.03